International competition in the war against Syria (United States of America - Russia) as a model - حسن عبد الوهاب; خالد المصري (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The aim of the research is studying the impact of Geopolitical justifications and Realistic data on the presence of the major powers in the War against Syria , which is of geostrategic weight, raising the pace of competition regarding it between regional and international powers. And has become an engine for the strategies of the major powers and their international calculations in the vital Middle Eastern arena that world interests intertwine. The most prominent example of this is the ongoing competition between the United States of America and Russia in Syria after 2011, which is the most important and largest global power involved in the international competition in the War against Syria . The geopolitical dimension - on the one hand - which explains the competition between these forces by virtue of the fact that Syria enjoys great importance from the geopolitical and strategic sides in international politics, which made it a center of polarization and attraction for international powers. On the other hand, to understand the geostrategic dimension in its explanation of the role of the major powers in the War against Syria . this role must be linked to the assumptions of political realism based on conflict and competition, and the primary role of the state in that regardless of the role of international organizations, and on the variable basis of the national interest and power. Which reflects the efforts of these international parties - especially Russia and the United States - to achieve their geostrategic interests and objectives in the Syrian geography, which conflict with the objectives and interests of the other party.